Design of Class F Power Amplifier for Sub 6 GHz - Akila, I.S.; Anitha, B.; Indhumeena, N.M.; NithiyaShri, D. (Journal of Electronics and Informatics, 2023)
Class F power amplifiers increasingly have widespread use cases in the modern portable mobile communications and higher efficiency operation due to base station. This paper focuses on the design of sub 6 GHz class-F Power Amplifiers (PA) to ensure maximum output power and gain using Gallium nitride– High Electron Mobility Transistor (GaN HEMT). The work also aims to analyze stability and Power Added Efficiency (PAE) using Advanced Design System (ADS) software. Simulations for DC characteristics of the GaN HEMT transistor are performed, stability circles are simulated, and stability factor values have been noted, using ADS software. Stability analysis involves measurements to examine the conditions that may lead to unstable behavior of the PA. The load pull analysis followed by impedance matching is done to transfer maximum power from amplifier stage to load. The input and output network has been designed using transmission lines and incorporated in the final circuit of the PA design. Using the LineCalc tool, the values of electrical parameters are used in the respective MLIN and TLIN circuits, and the respective matching networks are designed at the input side and output side. The amplifier stability factor is 2.276 and the maximum PAE is 65.75%. The maximum output is 39.83 dBm. The layout for the PA network using ADS software has been obtained.
Keywords: Class F power amplifier; GaN; HEMT; Stability analysis; Impedance matching; LineCalc; Input output matching; ADS